STRUKTUR BIROKRASI DAN DISPOSISI DALAM PELAKSANAAN KAWASAN SEHAT BEBAS ASAP ROKOK DI SEKOLAH - Purnomo, Parmadi Sigit; Sundoro, Totok; S, Pramukti Dian (Jurnal Cakrawala Promkes, 2020)
Based on the Health Research and Development Agency in 2013, the Special Province of Yogyakarta tended to be high at 21.2% for the proportion of the population aged over or equal to 10 years who smoked every day. One of the districts in the Yogyakarta Special Region that has a policy on non-smoking areas is Bantul Regency. The regulation regarding the non-smoking areas is regulated in the Bantul Regent's Regulation No. 18 of 2016 concerning Healthy Areas Non-Smoking (HANS). This study aims to determine the structure of the bureaucracy and disposition in the implementation of a Healthy Smoke Free Area in Schools. This research uses descriptive qualitative method. Data analysis using data reduction, data presentation, and drawing conclusions.Â  The results of interviews about the bureaucratic structure in the implementation of the HANS found that there were no smoking procedures for smokers in schools. General rules are included in the school code of conduct in the form of a slogan / smoking ban. The disposition aspect possessed by the school could not be said to be good in the implementation of the HANS, it was evident that there were still school residents who still smoked in the school area and found cigarette putp in the school area. The conclusion of the research is that the bureaucratic structure does not yet exist and the disposition factor cannot be carried out properly so that it is expected that there will be a follow-up from the Government of Bantul Regency to be able to socialize Bantul Regent Regulation No. 18 of 2016 concerning Smoke-Free Healthy Areas in the school environment involving the role of the Health Office, BNNP and / or the Police and develop a culture of reporting and providing guarantees for reporters from the Principal, as well as making special regulations / SOPs for school residents who have a smoking habit.